2019
DOI: 10.5114/ppn.2019.84356
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine and maintenance electroconvulsive therapy in a 35-year-old patient with treatment-resistant schizophrenia and chronic imperative auditory hallucinations

Abstract: Purpose: Despite progress in the treatment of schizophrenia, treatment resistance is reported in about 30% of patients. Various forms of treatment augmentation are used, but clozapine is generally considered to be the gold standard of care. In the management of patients with clozapine resistance adjunctive electroconvulsive therapy (ECT) courses have been proposed. In recent years particular attention has been paid to augmentation of clozapine with the maintenance electroconvulsive therapy (M-ECT). Case descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…They are most often not used as a single or exclusive method, but usually in combination with continued pharmacotherapy. Zakowicz et al (2019) showed that the use of ECT and clozapine in patients with drug-resistant schizophrenia (clozapine 600 mg/day, ECT every 3 weeks for more than a year) resulted in significant clinical improvement, with a reduction in perception disorders and elimination of aggressive and suicidal behaviour. A 2019 meta-analysis of 2,074 schizophrenia patients published in the Molecu lar Neuropsychiatry journal found that patients treated with ECT had a significantly reduced rate of psychiatric hospitalisation.…”
Section: { Introductionmentioning
confidence: 99%
“…They are most often not used as a single or exclusive method, but usually in combination with continued pharmacotherapy. Zakowicz et al (2019) showed that the use of ECT and clozapine in patients with drug-resistant schizophrenia (clozapine 600 mg/day, ECT every 3 weeks for more than a year) resulted in significant clinical improvement, with a reduction in perception disorders and elimination of aggressive and suicidal behaviour. A 2019 meta-analysis of 2,074 schizophrenia patients published in the Molecu lar Neuropsychiatry journal found that patients treated with ECT had a significantly reduced rate of psychiatric hospitalisation.…”
Section: { Introductionmentioning
confidence: 99%